Outcome of systemic therapy in patients with advanced rare skin cancers: a retrospective multicenter DeCOG study of 209 patients - Ugurel, Selma; Abu Rached, Nessr; Gambichler, Thilo; Mengoni, Miriam; Tüting, Thomas; Hassel, Jessica C.; Reschke, Robin Niklas; Lodde, Georg Christian; Placke, Jan-Malte; Schadendorf, Dirk; Reinhardt, Lydia; Kreuter, Alexander; et al. (European journal of cancer, 2025)
Introduction - For rare skin cancers, few data exist on the outcome of systemic therapies, particularly immune checkpoint inhibition (ICI). The present study analysed the real-world use of different systemic therapies including ICI, and its outcome in patients with advanced rare skin cancers. - Methods - This retrospective multicenter study included patients who received systemic therapy for advanced, non-resectable cutaneous angiosarcoma (AS), Kaposi sarcoma (KS), pleomorphic dermal sarcoma (PDS), or cutaneous adnexal carcinoma (CAC). Study endpoints were best overall response (BOR), progression-free survival (PFS) and overall survival (OS). - Results - 209 patients (77 AS; 81 KS; 14 PDS; and 37 CAC) from 30 centers were included. As first-line treatment AS and KS patients predominantly received chemotherapy (77.9%; 63.0%), while PDS and CAC patients mostly received ICI (64.4%; 43.2%). BOR in first-line across all therapy types was 65.5% in KS, 50.0% in PDS, 41.6% in AS, and 10.8% in CAC. BOR for ICI was 66.6% for PDS, 58.3% for AS, 33.3% for KS, and 4.3% for CAC, irrespective of treatment line. 1-year PFS rate upon any first-line therapy was 70.7% for PDS, 45.7% for KS, 25.6% for AS, and 18.5% for CAC (p<0.001). 1-year tumor-specific OS rate was 97.3% in KS, 84.2% in AS, 67.7% in PDS, and 65.4% in CAC (p<0.001). - Conclusions - Type and outcome of systemic therapy differed between cancer entities. Efficacy of ICI was high in PDS and AS, moderate in KS, and low in CAC. Patients with advanced CAC revealed an extremely poor prognosis regardless of the type of therapy used.